Екологічні проблеми агросистем Волинської області та їх вирішення - Потапова, Алла Геннадіївна; Potapova, Alla H. (Чернівецький національний університет ім. Ю. Федьковича, 2009)
Agriculture is closely connected with the use of natural resources. Every year the use of waters and other natural resources increases. High ploughing of agricultural lands multiplied a little gross yield of agricultural cultures but reduced the indexes of land fertility, deepened an ecological crisis, broke the environmental system, natural equilibrium and strengthened erosive processes. There is a question about forming highly productive L C and ecologically stable agro-systems taking into account different influence of natural conditions and resources on an agricultural production. Ecologization of land use helps to reproduce and increase land fertility. And to attain it possible due to a fight against erosion land, by support of self-supporting balance of humus and other nutritives, qualitative use of organic fertilizers, cultural technologic land-reclamation, making land-protective technologies. Measures of maintainance of land fertility, protection and cultivating of natural agro-landscapes, creation of the system of Held-protective forests, making afforestation of steep slopes, biological methods of defence of plants have priority before application of different chemical facilities and use of powerful technique with the large loading on land cover in agriculture. Changes which destroy land cover, are because of improved economic decisions, unbalanced anthropogene loading on agro-landscapes, increasing specific weight of the cultivated cultures, failure of crop rotations, reducing the total number of livestock of agricultural animals and decreasing of application of fertilizers and land-improvement. The basic levers of management of land fertility and crop capacity, which must be paidattention on, especially under the ; conditions of the high farming. For providing ecological equilibrium of territories it is recommended, that green crops occupied third of area of crop rotation. The particle of the cultivated cultures must not be outside scientific norms in the proper crop rotations. The ecological situation of region needs considerable alkalization and afforestation of cultivated lands.
Ecological Problems of Volyn Agro-Systems and Their Determination
Keywords: agro-landscape; lands degradation; balanced development of land use